2007
DOI: 10.1007/s11661-007-9349-5
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Nitinol under Quasistatic and Dynamic Loading

Abstract: Owing to the potential application of Nitinol as an advanced structural material, it is essential to thoroughly understand the deformation and fracture behavior of Nitinol under various loading conditions. The present study explores the fracture behavior of Nitinol under quasistatic and dynamic loading, with emphasis on the fracture toughness and fracture mechanism of Nitinol. To this end, the precracked bend sample was employed to perform dynamic fracture testing using a modified (pulse-shaped) Hopkinson-pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Yet another factor, which may influence the trigger stress for SIMT is strain rate. Although few studies relating the effect strain rate [11,[18][19][20][21][22] on the trigger stress for SIMT in NiTi based alloys have been carried out, no information is available in the literature on the effect of strain rate on trigger stress for SIMT in Ti-Al-Nb alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another factor, which may influence the trigger stress for SIMT is strain rate. Although few studies relating the effect strain rate [11,[18][19][20][21][22] on the trigger stress for SIMT in NiTi based alloys have been carried out, no information is available in the literature on the effect of strain rate on trigger stress for SIMT in Ti-Al-Nb alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was employed for delamination strength and toughness measurement, crack initiation, propagation and arrest behavior in an array of materials [32][33][34][35][36]. A variant of the 4PB specimen, double-notched 4PB specimen, has been employed to investigate the fracture mechanism of materials under both low [37,38] and high [39] loading rates. In this work, an attempt was made to validate the 4PB test with the detection of crack initiation in measuring the fracture toughness of the CFR-MIL composites that are more ductile than ceramics.…”
Section: Fracture Toughness Testingmentioning
confidence: 99%
“…The effect of triaxiality has been confirmed through quasi-static tensile testing of notched specimen and plane-strain fatigue crack growth studies [70,71], which showed that the triaxial stress constraint suppresses SIM transformation. However, higher strain-rates tend to produce mixed-mode (ductile void and cleavage) type failure mechanism [44,72]. Recent high-strain-rate fracture toughness studies of Ni-Ti [72] have also shown that the superelastic material exhibits a high amount of ductile void growth ( Fig.…”
Section: Fractography and Fracture Mechanismsmentioning
confidence: 99%
“…However, higher strain-rates tend to produce mixed-mode (ductile void and cleavage) type failure mechanism [44,72]. Recent high-strain-rate fracture toughness studies of Ni-Ti [72] have also shown that the superelastic material exhibits a high amount of ductile void growth ( Fig. 12(g)) even though the quasistatic fracture surface exhibits only quasi-cleavage type failure (see Fig.…”
Section: Fractography and Fracture Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation